2000
DOI: 10.3758/bf03211819
|View full text |Cite
|
Sign up to set email alerts
|

A model of human performance on the traveling salesperson problem

Abstract: A computational model is proposed of how humans solve the traveling salesperson problem (TSP), Tests of the model are reported, using human performance measures from a variety of 10-,20-,40-, and 60-node problems, a single 48-node problem, and a single 100-node problem. The model provided a range of solutions that approximated the range of human solutions and conformed closely to quantitative and qualitative characteristics of human performance. The minimum path lengths of subjects and model deviated by averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 8 publications
2
82
0
1
Order By: Relevance
“…A number of theoretical accounts have suggested that how people solve TSPs is, in part, based on perceptual processes (Graham et al, 2000;MacGregor et al, 2000). It seems plausible that, for very simple problems, perceptual processing predominates but, as problem diffi culty increases, more analytical processes come into play.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of theoretical accounts have suggested that how people solve TSPs is, in part, based on perceptual processes (Graham et al, 2000;MacGregor et al, 2000). It seems plausible that, for very simple problems, perceptual processing predominates but, as problem diffi culty increases, more analytical processes come into play.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, human solution times per problem increase in proportion to the number of nodes (Graham et al, 2000;Pizlo, Stefanov, Saalweachter, Li, Haxhimusa, & Kropatsch, 2006). Other generally agreed-upon fi ndings are that human solutions are typically close to optimal (Graham et al, 2000;MacGregor & Ormerod, 1996;van Rooij, Schactman, Kadlec, & Stege, 2006;Vickers, Butavicius, Lee, & Medvedev, 2001) and rarely self-intersect (MacGregor, Ormerod, & Chronicle, 2000;van Rooij, Stege, & Schactman, 2003;Vickers, Lee, Dry, & Hughes, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This observation has motivated researchers to set out to identify the human strategy for solving TSPs and implement it in a computational model. In this paper, we take a closer look at one such model, the Convex-hull (CH) algorithm model proposed by MacGregor, Ormerod, and Chronicle (2000), and its purported fi t to human performance on the TSP (for altogether different modeling attempts for TSP see Graham, Joshi, & Pizlo, 2000;and Pizlo et al, 2006). The CH model of MacGregor et al (2000) is a formal algorithmic elaboration on the convex-hull hypothesis put forth by MacGregor and Ormerod (1996;see van Rooij, Stege, & Schactman, 2003, for an overall assessment of the empirical support for this hypothesis) that proposes that people construct solutions to the TSP by fi rst perceiving (and mentally sketching) the boundary of the point set (called the convex hull) and then inserting one by one the interior points in the tour.…”
Section: Introductionmentioning
confidence: 99%
“…The CH model of MacGregor et al (2000) is a formal algorithmic elaboration on the convex-hull hypothesis put forth by MacGregor and Ormerod (1996;see van Rooij, Stege, & Schactman, 2003, for an overall assessment of the empirical support for this hypothesis) that proposes that people construct solutions to the TSP by fi rst perceiving (and mentally sketching) the boundary of the point set (called the convex hull) and then inserting one by one the interior points in the tour. To investigate the extent to which this CH algorithm captures the process underlying human performance on the TSP, MacGregor et al (2000) compared tours produced by the algorithm (for different starting points and directions of travel) with tours produced by humans. They studied in particular random or semirandom point sets, and found that tours produced by model and participants resembled each other in terms of tour length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation